Mental health during the COVID-19 pandemic: exploring the role of psychological flexibility and stress-related variables - Prudenzi, Arianna; Graham, Christopher D.; Rogerson, Olivia; O'Connor, Daryl B. (Psychology & health, 2023)
Understanding the impact of the COVID-19 pandemic on mental health and the psychological factors associated can help inform subsequent interventions to protect psychological health. In particular, psychological flexibility has been shown to be an important target for intervention. The current study aimed to investigate associations between protective factors (state mindfulness, values and self-compassion) and risk factors (COVID-19 stress, worry and rumination) for mental health during the early stages of the COVID-19 pandemic. 439 participants completed three online surveys during the 1st wave of the pandemic in the UK: Time 1 (April 1-5th 2020), Time 2 (April 15-19th April), Time 3 (May 13-17th 2020). Measures of wellbeing, burnout and life satisfaction. Psychological health outcome measures were found to be lower (worse) than normative comparison data during the early stages of the UK lockdown, while COVID-19 stress and worry reduced over time. Multilevel models found that higher levels of trait and state measures of psychological flexibility and self-compassion were associated with better psychological health across time points. Higher levels of COVID-19 stress, worry and rumination were also associated with poorer psychological health. The results showed that mindfulness, values and self-compassion are potential targets for intervention.